The Balmis expedition of 1803 and the debate about the merits of Spanish colonialism - andrade, gabriel (Medicina Historica, 2020)
As with any other European imperial power, Spain has in recent decades been subject to postocolonial critiques for its rule over colonies. Admittedly, much blood was spilled during the conquest of the Americas, and Spanish rule of the colonies was despotic. But, the more benign aspects of Spanish colonial rule are often ignored. One particularly enlightened moment of Spanish colonialism was the Balmis expedition of 1803. In the Spanish colonies, smallpox had been rampant, and it had contributed to reducing indigenous population during the conquest. In colonial times, it persisted as a major public health problem. The Spanish monarchy then decided to organize a major vaccination expedition in the colonies, under the command of Francisco Javier Balmis. In this article, I review the importance of that expedition for the history of medicine. I also consider some of its ethical shortcomings, and the way it contributes to the current debate about the merits of Spanish colonialism.